Immunological association of inducible bronchus-associated lymphoid tissue organogenesis in Ag85B-rHPIV2 vaccine-induced anti-tuberculosis mucosal immune responses in mice. (16th July 2018) - Nagatake, Takahiro; Suzuki, Hidehiko; Hirata, So-ichiro; Matsumoto, Naomi; Wada, Yasuko; Morimoto, Sakiko; Nasu, Ayaka; Shimojou, Michiko; Kawano, Mitsuo; Ogami, Kentaro; Tsujimura, Yusuke; Kuroda, Etsushi; et al.
Abstract: We previously reported that Ag85B-expressing human parainfluenza type 2 virus (Ag85B-rHPIV2) was effective as a nasal vaccine against tuberculosis in mice; however, the mechanism by which it induces an immune response remains to be investigated. In the present study, we found that organogenesis of inducible bronchus-associated lymphoid tissue (iBALT) played a role in the induction of antigen-specific T cells and IgA antibody responses in the lung of mice intra-nasally administered Ag85B-rHPIV2. We found that expression of Ag85B was dispensable for the development of iBALT, suggesting that HPIV2 acted as an iBALT-inducing vector. When iBALT organogenesis was disrupted in Ag85B-rHPIV2-immunized mice, either by neutralization of the lymphotoxin pathway or depletion of CD11b + cells, Ag85B-specific immune responses (i.e. IFN γ-producing T cells and IgA antibody) were diminished in the lung. Furthermore, we found that immunization with Ag85B-rHPIV2 induced neutrophil and eosinophil infiltration temporally after the immunization in the lung. Thus, our results show that iBALT organogenesis contributes to the induction of antigen-specific immune responses by Ag85B-rHPIV2 and that Ag85B-rHPIV2 provokes its immune responses without inducing long-lasting inflammation. Abstract : A parainfluenza-based nasal vaccine induces formation of BALT in the lung